キルギス天山山脈グリゴレア氷帽のアイスコア中の雪氷藻類 - 本多, 愛美; 竹内, 望; 世良, 峻太郎; 藤田, 耕史; 岡本, 祥子; 直木, 和弘; Vladimr, Aizen; Megumi, Honda; Nozomu, Takeuchi; Syuntaro, Sera; Koji, Fujita; Sachiko, Okamoto; et al. (2010)
第32回極域生物シンポジウム ポスター発表 conference object